Optimizing Internal Communication for Leadership Service Delivery in Local Government - Wa Ode Suci Fitriani; Muhammad Hidayatullah; Harry Fajar Maulana (Jogjakarta Communication Conference (JCC), 2026)
This study focuses on analyzing the internal communication patterns within the Protocol and Leadership Communication Section (PROKOPIM) of the Baubau City Regional Secretariat, with the aim of enhancing leadership service delivery. The research employed a qualitative, descriptive approach, utilizing in-depth interviews, observations, and document analysis. The study reveals that effective internal communication, characterized by intensive coordination, well-structured scheduling, two-way communication to resolve issues, adherence to protocol, and strong team cohesion, is essential for the smooth execution of leadership tasks. Findings indicate that communication tools such as WhatsApp and social media play a vital role in ensuring timely coordination, while regular briefings improve transparency and alignment. The study contributes to the literature by exploring the specific communication dynamics within local government organizations and their impact on leadership efficiency. The findings have practical implications for improving communication strategies in the public sector. Future research could focus on the role of digital communication platforms in enhancing public sector communication and examine the broader applicability of these findings in other local government settings.